Industrial policy and the WTO - Bora, Bijit; Lloyd, Peter J.; Pangestu, Mari 1956- (United Nations, 2000)
This paper aims to review the objectives and instruments of industrial policy in a changing global context. It addresses such issues as: justification for industrial policy; importance of analytical framework; the use of different instruments for industrial policy; role of industrial policy in the post-Uruguay Round era; and the possibilities and implications of revising rules that affect the use of industrial policy instruments--Publisher's description.
Keywords: Organisation mondiale du commerce; Organización Mundial de Comercio; World Trade Organization; AUTOMOBILE INDUSTRY; COMERCIO INTERNACIONAL; Commerce extérieur - Réglementation; DEVELOPING COUNTRIES; EAST ASIA; ECONOMIC LIBERALIZATION; EXPORT PROMOTION; FOREIGN DIRECT INVESTMENT; IMPORT RESTRICTIONS; INDONESIA; INDUSTRIAL POLICY; INDUSTRIAL PROMOTION; Industriepolitiek; POLITICA COMERCIAL; POLITICA INDUSTRIAL; PROTECTIONISM; Politique industrielle; TECHNOLOGICAL CHANGE; TECHNOLOGY TRANSFER; TRADE AGREEMENTS; TRADE POLICY; Commercial policy; Industrial policy; International trade; Industriepolitik